Pattern-oriented design for multi-agent system: a conceptual model - Mohamad, Radziah; Safaai, Deris; Ammar, Hany H. (ETH Zurich, 2007)
Design patterns represent solutions to specific problem of developing one application that have evolved over time. They leverage the reuse level to the design phase by providing a common vocabulary of design, means of understanding designs and proven building blocks from which more complex applications are built. Much of the research work on design patterns in agent world has primarily focused on discovering and documenting patterns. To reap the benefits of deploying these proven design solutions, patterns should be used as a first-class modelling blocks in designing the agent application. This paper proposes a conceptual model based on patterns and agent abstraction.